On-Body Transmission Single-Band Diamond Dipole Antenna with Waveguide Jacket - M. A. Abdullah; M. K. A Rahim; N. A. Samsuri; K. Kamardin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents the investigation of on-body transmission single-band diamond dipole antenna with three different jackets. The jackets are named as normal jacket, grounding jacket and waveguide jacket. The on-body transmission is measured using two flexible single-band antennas attach to the jackets. A man with the height of 180 cm and 75 kg weight becomes as a model for the real measurement. The measurement is conducted in small space area by using portable network analyzer with flexible network cable. The measurement results show that the best performance for on-body transmission is with waveguide jacket. 10 dB transmission improvement is archived when the antenna is placed above the waveguide jacket compared to the normal jacket. It is found that the transmission of the antenna is also depends on the antenna orientation and further transmission lossess occur when the antennas are placed above the grounding jacket.